Dietary bile acids supplementation modulates immune response, antioxidant capacity, glucose, and lipid metabolism in normal and intrauterine growth retardation piglets - Liu, Yang; Azad, Md. Abul Kalam; Kong, Xiangfeng; Zhu, Qian; Yu, Zugong (Frontiers in Nutrition, 2022)
Intrauterine growth retardation (IUGR) results in intestinal dysfunction contributing to metabolic syndrome and growth lag of piglets. Bile acid (BA) presents various bioactivities, including regulation roles in antioxidant, anti-inflammation, and glucolipid metabolism. Forty-eight weaned piglets were assigned into four groups in a 2 × 2 factorial arrangement with the effects of BA supplementation and IUGR challenge. Twenty-four IUGR piglets and 24 normal birth weight (NBW) piglets were allocated into two groups, respectively, including a control group fed with a basal diet, and the treatment group fed a basal diet supplemented with 400 g/t BA. The experiment lasted 28 days. The results showed that dietary BA supplementation improved liver and spleen index in IUGR piglets, whereas decreased blood RDW-CV and RDW-SD regardless of IUGR. Dietary BA supplementation decreased plasma CAT activity and liver GSH concentration regardless of IUGR, whereas increased plasma GSH and liver H2O2, and decreased liver T-AOC in weaned piglets (P < 0.05). In addition, IUGR downregulated (P < 0.05) liver Nrf1 and Nrf2 expression, while dietary BA supplementation upregulated (P < 0.05) Nrf2 expression of liver in weaned piglets. Dietary BA supplementation decreased (P < 0.05) jejunal GSH concentration and ileal CAT activity regardless of IUGR. Furthermore, IUGR upregulated (P < 0.05) jejunal SOD and CAT expressions; however, dietary BA supplementation upregulated ileal Nrf1 and Keap1 expression in piglets regardless of IUGR (P < 0.05). Moreover, IUGR upregulated the expression level of liver lipid synthesis (FAS) and downregulated the liver HSL and SCD1, while dietary BA supplementation downregulated (P < 0.05) FAS and SCD1 expression of liver. However, BA supplements could enhance liver gluconeogenesis by upregulating (P < 0.05) G6PC and PCK1 expression of liver in the NBW piglets but not in the IUGR piglets. Collectively, these findings suggest that dietary BA supplementation could regulate the redox status of weaned piglets by regulating the Nrf2/Keap1 pathway and improving liver glucolipid metabolism of IUGR piglets. These findings will provide a reference for the application of BA in swine production; moreover, considering the physiological similarity between pigs and humans, these findings will provide a reference for IUGR research in human.